ANALISIS PENERAPAN HIGIENE SANITASI PENGELOLAAN MAKANAN DI RUTAN KELAS II B KABUPATEN HUMBANG HASUNDUTAN TAHUN 2021 - Manalu, Lenni; Ketaren, Otniel; Ester J.Sitorus, Mido; Nababan, Donal; Lina Tarigan, Frida; Wandra, Toni (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2021)
Â Hygiene and sanitation is an important aspect in food processing, its application must be analyzed for improvement efforts. Analysis of the application of hygiene and sanitation of catering services by comparing with the standards of sanitation hygiene, Regulation of the Minister of Health of the Republic of Indonesia Number 1096/MENKES/PER/VI/2011 concerning Food Sanitation Hygiene.Methods: This type of research is a qualitative research that provides analysis results of the application of hygiene and sanitation of catering services. Data were collected by observation, interviews, and documentation studies. The data that has been obtained is then discussed and compared with the Regulation of the Minister of Health of the Republic of Indonesia Number 1096/MENKES/PER/VI/2011 concerning Food and Service Sanitation Hygiene.Results: Hygiene and sanitation analysis includes 6 Principles of Food Management Aspects, Physical Sanitation Aspects, Food Handlers Aspects.Conclusion: Analysis of the application of food management sanitation hygiene in Rutan Class II B, Humbang Hasundutan Regency in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 1096/MENKES/PER/VI/2011 concerning the Sanitation Hygiene of Jasaboga. The advice given is to maintain all indicators of achievement of 6 principles of food management principles, aspects of physical sanitation and aspects of food handlers' actions. Keywords: Sanitation Hygiene, Food Management PlacesÂ Keywords: Sanitation Hygiene, Food Management Places